Ethanol production from okra (hibiscus esculentus) stalk using acid and enzymatic hydrolysis (2018)
Bioethanol was produced from okra (Hibiscus esculentus) stalk, a waste agricultural residue using both acid and enzymatic hydrolysis. Acid hydrolysis was carried out on okra stalk using microwave as a medium of heat. The microwave power, heating time and acid concentration were 300Watts, 13.2min and 2M, respectively. After heating the pH was adjusted to 4.5 and yeast (Saccharomyces cerevisiae) was added to induce fermentation at room temperature. Enzymatic hydrolysis was carried out using the acid hydrolysis as a pre-treatment method, the mixture was detoxified using calcium chloride. Alpha amylase and glucoamylase enzymes were added for liquefaction and saccharification at optimum condition (6.5, 60oC), (5.0, 55oC) pH and temperature respectively. Yeast (Saccharomyces cerevisiae) was introduced at pH 4.5 at room temperature. The resultant mixture of the acid and enzymatic hydrolysis processes was filtered and distilled at 78oC and the properties of the ethanol determined. The ethanol yields from acid and enzymatic hydrolysis were 8.5ml and 12.9ml, respectively. The flash points (20.5oC, 22.5oC), pour points (5.77, 5.12), cloud points (20.26oC, 21.76oC), specific gravities at 29oC, were (0.892, 0.920), kinematic viscosities (1.25mm2/s, 1.29mm2/s), moisture contents (0.52, 2.00) and densities (0.970g/cm3, 0.982g/cm3) from acid and enzymatic hydrolysis process respectively were in-line with the ASTM specification for Bioethanol. Okra stalk was successfully used to produce bioethanol using acid and enzymatic methods at 300Watts, 13.2min and 2M of acid.